Outcome Comparison between Solumedrol and Dexamethasone in Moderate to Severe COVID Disease - Aleena Muzaffar, Saima Aslam, Sarmad Khalil, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Covid 19 is a disease caused by a virus belonging to SARS Co V2 family of viruses. It primarily effects the lungs resulting in inflammation and pneumonia. Objectives: The main objective of the study is to compare the outcomes and efficacy of solumedrol and dexamethasone in moderate to severe COVID disease. Material and methods: This cross sectional study was conducted in THQ Hospital Safdarabad during 2020 to 2021. The data was collected from 100 COVID-19 patients diagnosed with moderate to severe condition of the diseases. The data was collected through non-probability consecutive sampling technique. Results: The data was collected from 100 patients of moderate to severe COVID-19 condition. There were 35 patients in group I and 65 patients’ group II. The mean age for dexamethasone (group II) was 55.41 ± 10.4 years and solumedrol (group I) was 56.86 ± 9.3 years. Conclusion: It is concluded that both drugs dexamethasone and solumedrol are effective in improving clinical and biochemical parameters of moderate to severe covid 19 disease.